Cost and cost-effectiveness of a real-world HCV treatment program among HIV-infected individuals in Myanmar. Issue 2 (24th February 2021) - Marquez, Lara K; Chaillon, Antoine; Soe, Kyi Pyar; Johnson, Derek C; Zosso, Jean-Marc; Incerti, Andrea; Loarec, Anne; Nguyen, Aude; Walker, Josephine G; Mafirakureva, Nyashadzaishe; Lo Re III, Vincent; Wynn, Adriane; et al.
Abstract : Introduction: Over half of those hepatitis C virus (HCV)/HIV coinfected live in low-income and middle-income countries, and many remain undiagnosed or untreated. In 2016, Médecins Sans Frontières (MSF) established a direct-acting antiviral (DAA) treatment programme for people HCV/HIV coinfected in Myanmar. The purpose of our study was to evaluate the real-world cost and cost-effectiveness of this programme, and potential cost-effectiveness if implemented by the Ministry of Health (MoH). Methods: Costs (patient-level microcosting) and treatment outcomes were collected from the MSF prospective cohort study in Dawei, Myanmar. A Markov model was used to assess cost-effectiveness of the programme compared with no HCV treatment from a health provider perspective. Estimated lifetime and healthcare costs (in 2017 US$) and health outcomes (in disability-adjusted life-years (DALYs)) were simulated to calculate the incremental cost-effectiveness ratio (ICER), compared with a willingness-to-pay threshold of per capita Gross Domestic Product in Myanmar ($1250). We evaluated cost-effectiveness with updated quality-assured generic DAA prices and potential cost-effectiveness of a proposed simplified treatment protocol with updated DAA prices if implemented by the MoH. Results: From November 2016 to October 2017, 122 with HIV/HCV-coinfected patients were treated with DAAs (46% with cirrhosis), 96% (n=117) achieved sustained virological response. Mean treatment costs were $1229 (without cirrhosis) and $1971 (with cirrhosis), with DAA drugs being the largest contributor to cost. Compared with no treatment, the program was cost-effective (ICER $634/DALY averted); more so with updated prices for quality-assured generic DAAs (ICER $488/DALY averted). A simplified treatment protocol delivered by the MoH could be cost-effective if associated with similar outcomes (ICER $316/DALY averted). Conclusions: Using MSF programme data, the DAA treatment programme for HCV among HIV-coinfected individuals is cost-effective in Myanmar, and even more so with updated DAA prices. A simplified treatment protocol could enhance cost-effectiveness if further rollout demonstrates it is not associated with worse treatment outcomes.